Defects detection of main pipelines by vibroacoustic control systems - V. A. Komarov; A. A. Fedotov; L. A. Denisova (Омский научный вестник)
The article deals with defects detection in main pipelines through use of active vibroacoustic control systems of their condition. Descriptions and principles functioning of systems based on using probabilistic recognition methods of technical condition are presented. The results of numerical experiments are presented and dependences of defect detection error estimates on the acoustic noise intensity are obtained. It is shown that the use of active vibroacoustic control systems can effectively detect the defect in pipeline (incut, pit) even at small values of the signal/noise ratio.